Diversion Toward Juvenile Crime In South Sulawesi - Ririn Nurfaathirany Heri (Yuridika, 2022)
Juvenile offenders do not all end in diversion. According to Article 7 of the Juvenile Criminal Justice System Law, there are two categories that cannot get diversion, namely children who commit repeat crimes or are recidivist, and children who commit criminal acts and are threatened with coaching 7 years and over. Diversion is given when it has obtained approval from various parties, and a diversion agreement is reached by the victims and their families, the perpetrators and their families. Diversion deliberation does not always end well; if no agreement is reached, then the diversion is considered a failure or unsuccessful. Besides that, diversion can also fail if the perpetrators reject it. This research is a legal research. using a case approach, a conceptual approach and a statutory approach. The focus of the research is the target to be observed or measured, namely the provision of diversion for juvenile offenders, as well as obstacles in efforts to provide diversion to juvenile offenders. Giving diversion to children in an effort to foster a sense of responsibility shows good results, seeing the enthusiasm of children who show remorse for their actions so that there is good faith to listen and learn to be better people in the future. The obstacles faced in efforts to provide diversion to children who are in conflict with the law are that the proposed diversion consultations are not all agreed upon by the conflicting parties because of the siri' culture among Bugis-Makassar and the community's paradigm of retaliation,which is still entrenched